Electrochemical and spectroscopic properties of twisted dibenzo[g,p]chrysene derivatives - Imai, Tomoya; Akasaka, Ryuhei; Yoshida, Naruhiro; Amaya, Toru; Iwasawa, Tetsuo (Beilstein Journal of Organic Chemistry, 2022)
Dibenzo[g,p]chrysene (DBC), which consists of a twisted naphthalene core with four fused benzene rings, is a promising framework for organic electronic materials. Therefore, the research for structure–property relationships is important for the design of DBC-based materials. Here, the electrochemical and spectroscopic properties of DBC derivatives were investigated, and the effects of substituents and torsion of the naphthalene moiety were examined based on density functional theory (DFT) calculations. All the substituted DBC derivatives showed higher oxidation potentials than that for DBC-H, even for compounds that contained an electron-donating group such as DBC-Me and DBC-SMe. DFT calculations clearly indicate that these higher oxidation potentials are due to the ineffective conjugation of the MeO group, which is oriented perpendicular to the benzene ring because of the steric repulsion of substituents on both sides. More specifically, the inductive effect of the MeO group is dominant rather than the mesomeric effect when the substituent is located at both sides of the MeO group. Concerning the torsion of the naphthalene moiety, the twisting results in a slight increase in the HOMO and a slight lowering of the LUMO. The twisting effect is much smaller than the conjugation effect of the MeO group. Absorption spectra of all the substituted DBC derivatives also showed a red-shift as compared to that for DBC-H. Concerning the luminescence, a strong photoluminescence was observed for DBC-H and DBC-Si.
Keywords: DFT calculation; dibenzo[g,p]chrysenes; fluorescent compounds; oxidation; polycyclic aromatic hydrocarbon (PAH); twisted acenes